2015
DOI: 10.1002/ab.21570
|View full text |Cite
|
Sign up to set email alerts
|

Hostility, flooding, and relationship satisfaction: Predicting trajectories of psychological aggression across the transition to parenthood

Abstract: Psychological aggression has been shown to have harmful effects on both partners, sometimes above and beyond the effects of physical aggression. However, very little is known about psychological aggression during the transition to parenthood. The transition to parenthood is a time where relationship satisfaction often declines and stress increases, which may put the couples at higher risk for psychological aggression. The purpose of this study was to examine if prenatal risk factors related to interpersonal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 112 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…We currently know little about the trajectory of psychological IPV over the transition to parenthood; however, previously published data from the current study found that men’s and women’s reports of psychological IPV remained relatively stable from pregnancy to two years postpartum (Sotskova, Woodin, & Gou, 2014). The extant literature has demonstrated the deleterious effects that exposure to parents’ psychological IPV has on children’s adjustment (Harold, Shelton, Goeke-Morey, & Cummings, 2004; Jenkins & Smith, 1991; Katz & Woodin, 2002).…”
mentioning
confidence: 60%
“…We currently know little about the trajectory of psychological IPV over the transition to parenthood; however, previously published data from the current study found that men’s and women’s reports of psychological IPV remained relatively stable from pregnancy to two years postpartum (Sotskova, Woodin, & Gou, 2014). The extant literature has demonstrated the deleterious effects that exposure to parents’ psychological IPV has on children’s adjustment (Harold, Shelton, Goeke-Morey, & Cummings, 2004; Jenkins & Smith, 1991; Katz & Woodin, 2002).…”
mentioning
confidence: 60%
“…The actor effect between avoidant attachment and dyadic adjustment for women was mediated by actor hostile conflict; however, the same pattern was only marginally significant for men. Studies of hostility are consistent with this gender difference (Baron et al ., ; Oka et al ., ; Sotskova et al ., ). For example, a prospective study found that greater female hostility predicted worse female dyadic adjustment, while greater male hostility failed to significantly predict worse male dyadic adjustment (Baron et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Hostility and anger appear to forecast relationship dissatisfaction, in both cross‐sectional (Oka, Whiting, & Reifman, ; Renshaw, Blais, & Smith, ; Sotskova, Woodin, & Gou, ) and longitudinal study designs (Baron et al ., ; Lorenz, Hraba, & Pechacova, ). Significant within‐person and cross‐dyadic effects have been found between hostility and relationship adjustment (Baron et al ., ; Oka et al ., ; Renshaw et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The most critical node in the networks of waves 1 and 2 was hostility, a psychological dimension of aggression known for its more detrimental impact on interpersonal relationships compared to physical aggression ( 62 ). Notably, hostility served as the connecting link between aggression and sleep disturbance in both waves, consistent with the findings of Sun et al ( 63 ).…”
Section: Discussionmentioning
confidence: 99%